Modelling and simulation of self-regulating pneumatic valves. Issue 3 (4th May 2017) - Pollok, Alexander; Casella, Francesco
ABSTRACT: In conventional aircraft energy systems, self-regulating pneumatic valves (SRPVs) are used to control the pressure and mass flow of the bleed air. The dynamic behaviour of these valves is complex and dependent on several physical phenomena. In some cases, limit cycles can occur, deteriorating performance. This article presents a complex multi-physical model of SRPVs implemented in Modelica. First, the working principle is explained, and common challenges in control-system design-problems related to these valves are illustrated. Then, a Modelica-model is presented in detail, taking into account several physical domains. It is shown, how limit cycle oscillations occurring in aircraft energy systems can be reproduced with this model. The sensitivity of the model regarding both solver options and physical parameters is investigated.